Dietary phytosterols induce infertility in female mice via epigenomic modulations - Yoshihide Yamanashi; Toko Komine; Yasushi Hirota; Hiroshi Suzuki; Yutaka Osuga; Tappei Takada (Communications Biology)
Abstract Dietary modifications to overcome infertility have attracted attention; however, scientifically substantiated information on specific dietary components affecting fertility and their mechanisms is limited. Herein, we investigated diet-induced, reversible infertility in female mice lacking the heterodimer of ATP-binding cassette transporters G5 and G8 (ABCG5/G8), which functions as a lipid exporter in the intestine. We found that dietary phytosterols, especially β-sitosterol and brassicasterol, which are substrates of ABCG5/G8, have potent but reversible reproductive toxicities in mice. Mechanistically, these phytosterols inhibited ovarian folliculogenesis and reduced egg quality by enhancing polycomb repressive complex 2-mediated histone H3 trimethylation at lysine 27 in the ovary. Clinical analyses showed that serum phytosterol levels were significantly and negatively correlated with the blastocyst development rate of fertilized eggs in women undergoing in vitro fertilization, suggesting that phytosterols affect egg quality in both humans and mice. Thus, avoiding excessive intake of certain phytosterols would be beneficial for female reproductive health.